SCREENING OF FUNGICIDES AGAINST SCLEROTIUM ROLFSII CAUSING STEM ROT OF GROUNDNUT - K. B. RAKHOLIYA (The Bioscan, 2015)
Stem rot of groundnut caused by Sclerotium rolfsii Sacc. has a major constraint and potential threat to successful groundnut cultivation. Therefore affords were made to screen the different systemic, contact and combination of fungicides in vitro condition against Sclerotium rolfsii. Among systemic fungicides carboxin, hexaconazole and propiconazole were found 100 % growth inhibitions at all concentrations. While. fosetyl-Al, thiophanate methyl and carbendazim were found least effective 27.78%,16.67% and 11.85%, respectively growth inhibition of S. rolfsii at 500ppm. Among non systemic fungicides, mancozeb was found 100 % growth inhibition of S. rolfsii at all concentrations, while sulphur, zineb and copper oxychloride were found least effective against S. rolfsii even at higher concentrations. Carbendazim 50 WP + mancozeb 75 WP (1:2 manual) gave cent per cent inhibition of fungus at 500 ppm. Cymoxanil 8 % + mancozeb 64 % and carbendazim 50 WP + thiram 75 WP (1:2 manual) were also gave cent per cent growth inhibition of the fungus at 1000, 1500 and 2000 ppm concentrations.